Sequential injection Lab-at-valve (SI-LAV) segmented flow system for kinetic study of an enzyme - Ponhong K. (2014)
A sequential injection-Lab-at-valve (SI-LAV) segmented flow system for kinetic study of an enzyme was developed. Air segments were introduced for separation of enzyme and substrate zones and separation of the stacked zones from the carrier solution which ensure the measurement of the initial rate and minimize the dilution/dispersion effect. The open- ended mixing chamber makes it possible to use air segments in the flow system without the need for additional air segment discarding steps. The enzyme horseradish peroxidase (HRP) kinetic parameters based on initial rate was used as a model study. The operation of the system is virtually the same as that of the conventional batch-wise process. The kinetic parameters (i.e. Km and Vmax) of HRP obtained using the proposed system agree well with those obtained using the batch-wise process as well. The proposed system offers additional benefits of volume down scaling, improved rapidity and automatic features that does not require a skillful operator. © 2011 Elsevier B.V. All rights reserved.